In Vitro Embryo Production in Water Buffalo - Hufana-Duran, Danilda; Duran, Peregrino G. (Journal of Buffalo Science, 2022)
In vitro embryo production (IVEP) is a promising tool with many applications in producing calves from genetically superior animals desired for propagation and in the conservation and revival of endangered species. The techniques of IVEP were adopted from cattle and refined to suit the water buffalo requirements. From the collection of ovaries from a local abattoir and the collection of oocytes by ovum pick up from live animals, gamete storage, collection techniques, handling of ovaries and oocytes to keep the viability and developmental competence, selection of oocytes to the type of culture media and in vitro culture condition, and treatment of the sperm cells for in vitro fertilization are all-important components of the process that requires careful and precise action to ensure success. Trials on intracytoplasmic injection, the use of sex-sorted sperm cells as a tool for producing sex-predetermined embryos, and the somatic cell nuclear transfer are methods that can be used to produce embryos in vitro. This paper provides the important considerations involved in the production of healthy live calves out of in vitro-produced water buffalo embryos.